Giraffa camelopardalis_head - Lauridsen, Henrik; Hansen, Kasper; Nørgård, Mathias Ø.; Wang, Tobias; Pedersen, Michael (Dryad Digital Repository, 2016)
Interactive PDF model of Giraffa camelopardalis head. To activate the 3D feature click the model. Using the cursor it is now possible to rotate, zoom, pan the model and in the model tree all segments of the model can be turned on/off or made transparent.